Production of bioethanol from rice straw using cellulase by local Aspergillus sp. - Roslan, Ahmad Muhaimin; Phang, Lai Yee; Md. Shah, Umi Kalsom; Abd. Aziz, Suraini; Hassan, Mohd Ali (Academic Journals Inc., 2011)
Cellulase production in situ was considered as one of the alternatives to reduce bioethanol production cost. In this study, cellulase enzyme was produced from rice straw by locally isolated Aspergillus sp. in solid state fermentation. The crude cellulase was measured to have activity of 6.3 FPU g-1 rice straw. The rice straw was pretreated by few cycles of wet disc milling prior saccharified it using the crude cellulase produced. More than 90% glucose from total cellulose was released by the saccharification. The saccharified product was subjected to fermentation by yeast. The highest bioethanol yield produced from the fermentation was 0.102 g g-1 rice straw which is equivalent to 62.61% of theoretical bioethanol yield. It was concluded that the use of crude cellulase from rice straw onto rice straw can lead to a good yield of bioethanol, provided an effective pretreatment was used.